Bullous lung diseases as a risk factor for lung cancer - A case report - Nagorni-Obradović, Ljudmila M; Pešut, Dragica P; Marić, Dragana; Stević, Ruža S (Vojnosanitetski pregled, 2017)
Introduction. A possible association between lung cancer and bullous lung disease has been suggested and recently supported by the results of genetic studies. Case report. A previously healthy 43-year-old man, smoker, was diagnosed with bullous lung disease at the age of 31 years. He was followed up for 12 years when lung cancer (adenocarcinoma) was found at the site. In the meantime, he was treated for recurrent respiratory infections. Conclusion. There is the need for active approach in following up the patients with pulmonary bulla for potential development of lung cancer.
Keywords: lung neoplasms; risk factors; bronchopneumonia; diagnosis; tomography; x-ray; computed; disease progression